Peran Kinesiologi dalam Peningkatan Kinerja Atlet: Tinjauan Terhadap Teknik dan Metode Latihan - Awal, Asri (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This study aims to comprehensively examine the implementation of cognitive and affective approaches in physical education and their implications for developing students’ character and social skills. A descriptive qualitative approach with a literature-based method was employed to analyze theoretical perspectives, pedagogical models, and empirical studies published between 2010 and 2025 from databases such as Google Scholar, ScienceDirect, Taylor & Francis, and SpringerLink. The findings indicate that instructional models such as Teaching Games for Understanding (TGfU) and Teaching Personal and Social Responsibility (TPSR) significantly enhance strategic thinking, self-reflection, social empathy, and moral responsibility among students. Furthermore, the physical literacy framework serves as an integrative approach that unites physical, cognitive, and affective domains to foster meaningful and holistic learning in physical education. Therefore, integrating cognitive and affective approaches contributes substantially to developing students who are intellectually capable, morally grounded, and socially resilient.